The ‘Chinese Dream’ or the ‘American Nightmare’: Where Did the U.S.-China Relations Come in Three Decades - Y. V. Leksyutina (Международная аналитика, 2021)
The bulk of academic studies characterize the contemporary U.S. – China relations as asymmetrical ones, in which the relations' agenda − a course towards ﬁnding areas of cooperation or emphasizing contradictions/rivalry − was set by Washington's policy towards China, with the latter being more of a reacting party. In this paper, I argue that one needs a further and deeper reﬂection on the current confrontation between the U.S. and China, in particular the reasons and circumstances of how and why the “Chinese dream” of a remarkable renaissance of the Chinese nation became an American nightmare, forcing Washington to opt for a containment policy against China. In this regard, I show the importance of tracing the dynamics of the post-Cold War development of the U.S. – China relations to comprehend the patterns and logic of the shaping of American policy towards China. The article also explains the evolution of U.S. – China relations in the post-Cold War period as determined by the presence or absence of a strategic basis in the U.S. – China relations, which implies cooperation between the two countries in stopping the external existential threat to the U.S. So, I conclude that the uniqueness of the current stage lies in the fact that, because of China's emergence as a strong global power and Washington's disillusions about China, China itself is beginning to be perceived by Washington as an existential threat, to stop which the containment policy should be applied.